Influência da luz e da temperatura sobre a oxidação do óleo essencial de capim-limão (Cymbopogon citratus (D.C.) Stapf) Influence of light and temperature on the oxidation of the essential oil of lemongrass (Cymbopogon Citratus (D.C.) Stapf) - Luiz Gustavo de L. Guimarães (Química Nova, 2008)
The identification of the chemical compounds of the essential oil was performed with a gas chromatograph coupled to a mass spectrometer. The oil was left in the presence and absence of light and submitted to different temperatures to evaluate its stability. The yields of the major compounds were evaluated every fifteen days. Citral and myrcene, the major compounds of the essential oil, were degraded over time in both the presence and absence of light, but temperature only influenced the degradation of myrcene.